Impact of COVID‐19‐related public health measures on HCV testing in British Columbia, Canada: An interrupted time series analysis. (13th October 2021) - Binka, Mawuena; Bartlett, Sofia; Velásquez García, Héctor A.; Darvishian, Maryam; Jeong, Dahn; Adu, Prince; Alvarez, Maria; Wong, Stanley; Yu, Amanda; Samji, Hasina; Krajden, Mel; Wong, Jason; et al.
Abstract: Background & Aims: Public health measures introduced to limit transmission of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), which causes coronavirus disease 2019 (COVID‐19), also disrupted various healthcare services in many regions worldwide, including British Columbia (BC), Canada. We assessed the impact of these measures, first introduced in BC in March 2020, on hepatitis C (HCV) testing and first‐time HCV‐positive diagnoses within the province. Methods: De‐identified HCV testing data for BC residents were obtained from the provincial Public Health Laboratory. Weekly changes in anti‐HCV, HCV RNA and genotype testing episodes and first‐time HCV‐positive (anti‐HCV/RNA/genotype) diagnoses from January 2018 to December 2020 were assessed and associations were determined using segmented regression models examining rates before vs after calendar week 12 of 2020, when measures were introduced. Results: Average weekly HCV testing and first‐time HCV‐positive diagnosis rates fell immediately following the imposition of public health measures by 62.3 per 100 000 population and 2.9 episodes per 1 000 000 population, respectively ( P < .0001 for both), and recovered in subsequent weeks to near pre‐March 2020 levels. Average weekly anti‐HCV positivity rates decreased steadily pre‐restrictions and this trend remained unchanged afterwards. Conclusions: Reductions in HCV testing and first‐time HCV‐positive diagnosis rates, key drivers of progression along the HCV care cascade, occurred following the introduction of COVID‐19‐related public health measures. Further assessment will be required to better understand the full impact of these service disruptions on the HCV care cascade and to inform strategies for the re‐engagement of people who may have been lost to care because of these measures.